VD_FINDINFO Décision / 2013 / 927 vom 7. November 2013 - VD Tribunal cantonal (2013)
DROIT D'ÊTRE ENTENDU, DROIT DE S'EXPLIQUER, RÉCUSATION, ASSISTANCE JUDICIAIRE | 136 CPP (CH), 318 CPP (CH), 56 CPP (CH)